Case for an international court of civil justice - Steinitz, Maya (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2019)
"When multinational corporations cause mass harms to lives, livelihoods, and the environment in developing countries, it is nearly impossible for victims to find a court that can and will issue an enforceable judgment. In this work, Professor Maya Steinitz presents a detailed rationale for the creation of an International Court of Civil Justice (ICCJ) to hear such transnational mass tort cases. The world's legal systems were not designed to solve these kinds of complex transnational disputes, and the absence of mechanisms to ensure coordination means that victims try, but fail, to find justice in country after country, court after court. The Case for an International Court of Civil Justice explains how an ICCJ would provide victims with access to justice and corporate defendants with a non-corrupt forum and an end to the cost and uncertainty of unending litigation - more efficiently resolving the most complicated types of civil litigation"--
Introduction : Adjudicating cross-border mass torts : a problem of forum, not just of law -- How new international courts come into being -- The human toll : the Bhopal disaster, the devastation of the Ecuadorian Amazon, and the abuse and murder of Dr. Kiobel -- The problem of the missing forum -- The business case for the ICCJ -- Institutional and procedural features of an ICCJ.
Includes bibliographical references and index.
Keywords: Tort liability of corporations; Liability for human rights violations; Liability for environmental damages; International courts; Complex litigation; Class actions (Civil procedure); Class actions (Civil procedure); Complex litigation; International courts; Liability for environmental damages; Liability for human rights violations; Tort liability of corporations; International courts; Civil justice; Violation des droits de l'homme.; Recours collectifs (droit).